(untitled) (Research, Society and Development, 2025)
Psychological assessment is one of the most complex practices in psychology, requiring professionals not only to possess technical expertise but also ethical rigor and social responsibility. This study aims to discuss the ethical principles that guide the use, administration, and interpretation of psychological tests, addressing aspects such as professional responsibility, confidentiality, scientific validity, and respect for the rights of the individual being assessed. This is a qualitative bibliographical study conducted through consultation of the CAPES portal (Theses and Dissertations) between 2010 and 2024, including guidelines from the Federal Council of Psychology (CFP) and international organizations such as the American Psychological Association (APA) and the International Test Commission (ITC). The results demonstrate that ethics in psychological assessment goes beyond mere compliance with technical standards, demanding critical reflection, contextual sensitivity, and discernment when faced with ethical dilemmas. Therefore, continuing education and ongoing training for psychologists are essential to ensure fair, scientifically valid, and socially responsible assessments. It is concluded that ethics must be understood as a constitutive part of the psychologist’s professional identity, guiding their practice in a critical, conscious and committed way to human dignity.